2016
DOI: 10.12659/msm.895086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Color-Changing Effect and Complications After Nd: YAG Laser Application On Iris Surface

Abstract: BackgroundThe aim of this study was to evaluate the color-changing effect and adverse effects after Nd: YAG laser application on the iris surface of rabbit eyes.Material/MethodsThe study was performed on right eyes of 12 pigmented rabbits. A laser device that produces frequency doubled 532 nm wavelength Nd: YAG laser with 900 μm spot diameter was used. The laser was applied in 3 sessions at 2-week intervals, at energy levels of 0.8 mJ in Group A and 1.5 mJ in Group B. Slit-lamp examinations and measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The Crystal Q-switched Nd: Yag laser (532 nm) with 3–4 ns pulses is shown to achieve a perfect depigmentation of the anterior iris, as was suggested in other studies. However, these two previous publications refer to an experimental work in rabbits [ 21 ], and a single clinical case of heterochromia [ 22 ]. Therefore, our study is the first in the world to establish all the scientifically proven bases, in a large series of patients and with a long follow-up time of 9 years, the first 5 years to compare four different types of laser and the last 4 years performed only with 532 nm/3–4 ns Nd: Yag Laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Crystal Q-switched Nd: Yag laser (532 nm) with 3–4 ns pulses is shown to achieve a perfect depigmentation of the anterior iris, as was suggested in other studies. However, these two previous publications refer to an experimental work in rabbits [ 21 ], and a single clinical case of heterochromia [ 22 ]. Therefore, our study is the first in the world to establish all the scientifically proven bases, in a large series of patients and with a long follow-up time of 9 years, the first 5 years to compare four different types of laser and the last 4 years performed only with 532 nm/3–4 ns Nd: Yag Laser.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in 2017, Yildirim et al published: “Evaluation of color-changing effect and complications after Nd: YAG laser application on iris surface”. An experimental study in rabbits, that confirmed good cosmetic results and safety [ 21 ], and also, in 2018, 1 year later, Basoglu et al [ 22 ] published: “The effect of SLT laser application on iris to treat sectorial heterochromia: A promising technique”.
Fig.
…”
Section: Introductionmentioning
confidence: 91%
“…The procedure uses a device mounted onto a slit-lamp biomicroscope that produces a frequency-doubled 532-nm wavelength neodymium: yttrium-aluminum-garnet (Nd:YAG) laser with different spot diameters. Yildrim et al [4] conducted an animal study using a 900-lm spot size: they applied 200 laser shots (A.R.C. Laser, Germany) in two groups of rabbits divided according to the energy levels (group A, 0.8 mJ; group B, 1.2 mJ) with a laser application time of 3 ns.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…The authors also observed ciliary injection and mild anterior chamber reaction in all groups on the first day, which became more prominent in group B and eventually disappeared after the first week. Nevertheless, they did not administer antiinflammatory treatment, and there was no hypopyon or prolonged anterior chamber reaction [4].…”
Section: Clinical Application Outcomes and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation